2002
DOI: 10.2214/ajr.178.4.1780859
|View full text |Cite
|
Sign up to set email alerts
|

Intrathoracic Migration of the Wrap After Laparoscopic Nissen Fundoplication

Abstract: Intrathoracic migration is an important complication of laparoscopic Nissen fundoplication. Most migrations are small and asymptomatic. We propose a simple and reproducible radiologic definition of two different types of intrathoracic migration of the wrap observed after laparoscopic Nissen fundoplication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
1
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 9 publications
1
19
1
2
Order By: Relevance
“…Postoperative herniation of the fundoplication into the chest is not an uncommon occurrence after laparoscopic fundoplication and has been reported to occur in as many as 30% of cases. 40 Most herniations are small and asymptomatic. Yet the presence of the wrap in the chest has been reported as one of the major etiologic factor behind the occurrence of perforations and GBF.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative herniation of the fundoplication into the chest is not an uncommon occurrence after laparoscopic fundoplication and has been reported to occur in as many as 30% of cases. 40 Most herniations are small and asymptomatic. Yet the presence of the wrap in the chest has been reported as one of the major etiologic factor behind the occurrence of perforations and GBF.…”
Section: Discussionmentioning
confidence: 99%
“…completely below the diaphragm; fundoplication partly herniated above the diaphragm but the GOJ remains below the diaphragm (Type I migration) ( Figures 3 and 4); fundoplication completely herniated above the diaphragm with the GOJ at or above the level of the diaphragm (Type II migration) ( Figure 5)] [14].…”
Section: Structured Report For Contrast Study Reviewmentioning
confidence: 99%
“…However, there is very little in the literature addressing the quality and accuracy of post-operative contrast swallows. One prior publication [14] found that agreement between two radiologists in differentiating partial (Type I) and total (Type II) wrap migrations was good (k50.84), but no mention was made of the accuracy of diagnosis nor of the interobserver reliability within and between upper gastrointestinal surgeons and radiologists. The aim of this study was to determine the accuracy and interobserver reliability of surgeons and radiologists in interpreting post-operative contrast studies following laparoscopic fundoplication.…”
mentioning
confidence: 99%
“…Im Anschluss an die Öso-phagoskopie traten erstmalig Schmerzen auf, welche nach der Bougierung an Intensität zunahmen und mit Dyspnoe einhergingen. Die vorliegenden Befunde lassen folgende Schlüsse zu: Während direkt postoperativ eine zu enge Manschette die Schluckstörung bedingte, könnte durch Erbrechen eine neu aufgetretene paraösophageale Hernie die Dysphagie verstärkt haben, ohne jedoch durch Schmerzen symptomatisch zu werden [4]. Die durchgeführte Ösophagoskopie erwies sich in der Diagnosefindung als unzuverlässig, da endoskopische Befunde schwierig zu interpretieren sind [5].…”
Section: Diskussionunclassified